Design and validation of low-cost handling equipment for the use of Barkhausen Noise Testing in worm gears grinding burn detection. Issue 1 (February 2021) - Citti, P; Molinari, P; Giorgetti, A; Polidoro, A; Pompei, L; Arcidiacono, G
Abstract: Worm gears in high-performance gearboxes are often exposed to extreme loads, which requires assuring high production quality. Therefore the most important final characteristics of the workpieces are provided by grinding. One of the most investigated issues of this machining method is grinding burns, who change locally the properties of the material. In many industrial applications, nital etching is used to detect grinding burn. Although it is considered a standard, new types of tests are of great interest in order to reduce costs and make online control possible. One of the Non-Destructive Testing methods is Barkhausen Noise Testing (BNT), which is utilized to assess changes in the surface layer of ferromagnetic materials, especially to monitor changes in their hardness and residual stresses. To obtain accurate measures using this technology the Barkhausen probe handling system is essential. Typically the sensor handling system is an Inline/robot component, an automated component, a semi-automated component, or a manual handling system. Considering this scenario, the use of a manual system could allow having important cost savings but has to be correctly developed to obtain reliable measures. The aim of this paper is to develop a handling equipment for the BNT probe able to assure an adequate level of accuracy and repeatability.